FINANCIAL PERFORMANCE ANALYSIS USING CAMELS AT PT. BANK SYARIAH INDONESIA BEFORE AND AFTER MERGER - Moch. Rusli (Universitas Muhammadiyah Surakarta, 2024)
This study discusses the comparison of the financial performance of PT Bank Syariah Indonesia (BSI) TBK before the merger of PT Bank Syariah Mandiri (BSM), PT Bank Rakyat Indonesia Syariah (BRIS), and PT Bank Negara Indonesia Syariah (BNIS) and after the merger became PT Bank Indonesian Sharia (BSI) TBK. This study aims to analyze the financial performance of PT BSI TBK before and after the merger using CAMELS, namely Capital, Assets, Management, Earnings, Liquidity, and Sensitivity of the Market with a focus on CAR, NPF, NPM, ROA, ROE, FDR, and PDN assessments. The method used uses descriptive quantitative analysis by analyzing annual reports through the company's website and accessed from www.idx.co.id. The data used consists of Islamic banking financial reports from BSM, BRIS, and BNIS before the merger, namely 2016-2020 and on BSI in 2021 and 2022. The results show that the ratio analysis of PT BSI TBK before the merger focuses on CAR, NPF, NPM assessment, ROA, ROE, FDR, and PDN yielded a value of 19.20%, 2.31%, 4.37%, 1.05%, 8.56%, 76.94% and PT BSI TBK after the merger, respectively are 21.19%, 0.72%, 6.18%, 1.80%, 15.28% and 76.38%. So these results indicate that the performance of financial ratios using the CAMELS method after the merger is better than the financial performance before the merger.